THE EFFECT OF THE VALUE ADDED TAX ACT AMENDMENT 2013 ON TAX REVENUE IN KENYA. - Muia Boniface Mutie, L’Souza Boniface Alubisia, Gichana Jay Murray (International Journal of Research Science and Management, 2018)
Kenya has been faced with the need to generate more tax revenue to support its expenditure on public services for both the national and county governments. With the ever-increasing budget deficit and increased borrowing to support itself, the cabinet secretary for treasury came up with drastic measures to increase VAT revenue in 2013. The objective of this study was to examine the effect of the VAT Act amendment 2013 on tax revenue in Kenya. The study used secondary data from the Kenya National Bureau of Statistics for the financial year 2006/7 to 2015/16 which provided sufficient dataset for the event study model of analysis used. The analysis result indicated that VAT revenue and total tax revenue exhibited a continuous growth in the study period. This study found that the amendment of the VAT Act in 2013 led to a general increase in VAT revenue. This was depicted by the sudden increase in domestic VAT revenue after amendment. The revenue growth was highest in the post-amendment period than before the amendment. The growth was more pronounced in the domestic VAT revenue than the import VAT revenue suggesting that consumption was more on the local products than the imports. The government could therefore ride on these findings to tighten any loopholes in the collection of VAT revenue from businesses in Kenya, concentrating more especially on the domestic products which brought in more VAT revenue than the imports.